Surah Al-Humaza: Invocation Objective Study - freihat, Shareefah abdulkareem (Journal of Islamic Sciences, 2019)
The objective interpretation can be showed in three ways: to follow the text in its context in the Koran and interpreted its meaning; to search for the similar verses which competent one subject and illustrates the objective interpretation; or to address the whole Surah and explore it in an objective study and to explain the definition of the Surah and determine the main idea of the Surah then divided into topics and link verses with the main idea.The aim of this study is to study Surat Al- Humaza an objective study, a general definition of the surah and its topics was explored then the topics were linked with the pre - and beyond to show the miracle the connection between the topics of the Koran in the context of the Surah and its verses. Then the main idea was identified which is challenging and flawing people in their presence and in their absence, then the topics of the verses of Surah were linked to the main idea to show “with the help of God” the objective unity of the Holy Qur'an.The first verse of the Surah threat and intimidate anyone who challenges people and flaw them, because challenging and flawing people showed the evil in the heart, and the behavior of the Muslim is correct only by treating his heart after the recovery of his mind. As money is one of the motives that drive the evil hearts to challenge and flaw the people and do unfairness to other people, the Surah stated the money and its impact on the souls after the threat and intimidation on the one who slanderer that he insults and holds others in contempt habitually, the fraud and raise money to arrogance and did not pay for the right of God for the poor will all be lost, crashed and shattered all hopes and. Every oppressor arrogant to the other will be punished in the Hell, all of this were sown in the Surah and it can be seen in the unity of objectivity between the verses of Surah from beginning to end.
Keywords: The Holy Quran; Surah Al-Humaza; Objective interpretation